Reorientating dental curricula to reflect a minimally invasive dentistry approach for patient‐centred management. (31st May 2013) - Kaidonis, JA; Skinner, VJ; Lekkas, D; Winning, TA; Townsend, GC
Abstract: Minimally invasive dentistry (MID), together with patient‐centred care (PCC), can be considered central to patient management. These approaches have been incorporated in the structure of various dental curricula and indeed formally assessed. However, there is limited evidence that students have an integrated skill‐set and are able to apply these skills when providing direct patient care within the clinical setting. Assessment of students' application of core clinical skills has identified numerous deficiencies that need to be addressed. The revised Bachelor of Dental Surgery curriculum at the School of Dentistry, The University of Adelaide, provides an example of how MID, underpinned by PCC, can be presented throughout a dental curriculum. Essentially, MID and PCC are not considered as separate subjects but as a patient management approach that is 'woven into the whole fabric' of the curriculum. The programme relies on the development of empathic communication skills that enable students to obtain key patient information, including their patients' values, beliefs, needs, preferences and expectations, thereby allowing management to be tailor‐made. As a result, patients are empowered to be a part of the oral health care team. The Adelaide undergraduate dental curriculum consists of one clinical stream called Dental Science and Practice (DSP), that promotes the application of student knowledge, skills and behaviours in the clinical setting. Vertical and horizontal integration, aligned with an integrated approach to assessment, drives the learning throughout the programme. Clearly‐defined outcomes are introduced by Integrated Learning Activities (ILAs) that provide a focus for associated learning activities (e.g. class meetings, tutorials, simulation laboratories, etc). The aim of this approach to learning and teaching is to ensure the required learning outcomes are achieved. It also requires coordinated teaching teams including trained external tutors who clearly understand all aspects of MID and PCC within the curriculum structure.